DC-link Oscillation Suppression Strategy Based on the Virtual Positive Impedance for Metro Traction Drive System - LI Tingting; HU Xiao; LIU Chuan; YANG Jing; GE Xinglai (Kongzhi Yu Xinxi Jishu)
Stable operation is of high importance for high-performance metro traction drive system. However, in practice, DC-link oscillation happens in the metro traction drive system, which may degrade the system performance. To address this issue, an active damping control strategy based on virtual positive impedance is proposed to suppress the DC-link oscillation in this paper. Deviation of DC-link voltage is obtained by combining actual DC-link voltage with a low-pass filter. Accordingly, the deviation of DC-link voltage is feed back to the control system, aiming at compensating the negative damping characteristic and consequently achieving satisfactory suppression of DC-link oscillation. Simulation and experimental results show the effectiveness of the proposed control strategy when the motor is running under rated load conditions.